2014
DOI: 10.1186/1471-2458-14-659
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing voluntary premarital medical examination in Zhejiang province, China: a culturally-tailored health behavioral model analysis

Abstract: BackgroundPremarital medical examination (PME) compliance rate has dropped drastically since it became voluntary in China in 2003. This study aimed to establish a prediction model to be a theoretic framework for analyzing factors affecting PME compliance in Zhejiang province, China.MethodsA culturally-tailored health behavioral model combining the Health Behavioral Model (HBM) and the Theory of Reasoned Action (TRA) was established to analyze the data from a cross-sectional questionnaire survey (n = 2,572) usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In addition, studies on individuals’ behavior changes toward infectious diseases have suggested that perceptions or beliefs about an outbreak are important in determining the adoption of particular preventive behaviors [ 22 - 24 ]. In particular, the health belief model (HBM) [ 25 ] has provided a theoretical framework in previous research for understanding and explaining various health-promoting behaviors [ 26 - 28 ], including preventive behaviors during global pandemics [ 29 - 31 ]. The HBM model reveals that significant perception factors include perceived severity, perceived susceptibility, and perceived benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies on individuals’ behavior changes toward infectious diseases have suggested that perceptions or beliefs about an outbreak are important in determining the adoption of particular preventive behaviors [ 22 - 24 ]. In particular, the health belief model (HBM) [ 25 ] has provided a theoretical framework in previous research for understanding and explaining various health-promoting behaviors [ 26 - 28 ], including preventive behaviors during global pandemics [ 29 - 31 ]. The HBM model reveals that significant perception factors include perceived severity, perceived susceptibility, and perceived benefits.…”
Section: Introductionmentioning
confidence: 99%
“…During the period 1995–2003, premarital medical examinations were mandatory for couples; however, this requirement was canceled in 2003. Currently, the premarital medical examination is voluntary, and its rate has been reduced by almost 50% ( 13 ). In addition, the National Stocktaking Report on Birth Defect Prevention (2012) revealed that the incidence of birth defects was 5.6%, with ~900,000 new cases reported annually in China.…”
Section: The History Of Preconception Care In Chinamentioning
confidence: 99%
“…21 To solve this issue while determining the relationship between the proposed factors, multilevel structural equation modeling (MSEM) is the best choice. 22 Currently, MSEM has been used in the fields of public health policy [23][24][25] and adolescent health, 26,27 but rarely in health technology use.…”
Section: Introductionmentioning
confidence: 99%